2009
DOI: 10.1007/s12199-009-0100-2
|View full text |Cite
|
Sign up to set email alerts
|

Common risk factors for changes in body weight and psychological well-being in Japanese male middle-aged workers

Abstract: Objectives Overweight and poor psychological wellbeing are becoming serious health issues in the Japanese workplace. Concurrence of those physical and mental conditions has been pointed out, especially in middle-aged workers. Therefore, we tried to determine common risk factors for body weight gain and the deterioration of psychological well-being in male middle-aged office workers using a five-year follow-up study. Methods We administered General Health Questionnaire-12 (GHQ-12) as an indicator of psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 48 publications
5
16
2
Order By: Relevance
“…SOC scores should be regarded as complementary to and not a substitute for information already known to be associated with an increased risk for future illness (Suominena et al 2001). Our results demonstrated that SOC scores within the low GHQ-12 group were significantly higher than those in the high GHQ group, which is consistent with previous studies (Matsuzaki et al 2007;Sagara et al 2009;Urakawa and Yokoyama 2009). Generally, the GHQ-12 has been used in primary health care screenings in general population surveys as well as in general medical practice (Doi and Minowa 2003).…”
Section: Discussionsupporting
confidence: 90%
“…SOC scores should be regarded as complementary to and not a substitute for information already known to be associated with an increased risk for future illness (Suominena et al 2001). Our results demonstrated that SOC scores within the low GHQ-12 group were significantly higher than those in the high GHQ group, which is consistent with previous studies (Matsuzaki et al 2007;Sagara et al 2009;Urakawa and Yokoyama 2009). Generally, the GHQ-12 has been used in primary health care screenings in general population surveys as well as in general medical practice (Doi and Minowa 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Previous cross-sectional studies in female populations have reported an association between SOC and blood pressure [30], type 2 diabetes [31] and dyslipidemia [9]. The study in Japanese male, middle-aged workers has suggested that a weak SOC may be a risk factor for weight gain [8]. The present study also showed that SOC is associated with overweight, dyslipidemia and elevated blood sugar level.…”
Section: Characteristics Of the Participantssupporting
confidence: 70%
“…To our knowledge, there are no published studies demonstrating an association between SOC and both multiple atherosclerotic risk factors, including MetS, and lifestyle behaviors in the same subjects. However, there are a few studies that have shown an association between SOC and objective physical health [8,9]. We aimed at examination of the hypothesis that a strong SOC, in Japanese computer IJOMEH 2014;27(6) 969 in Japan (Table 1) [10].…”
Section: Periodical Health Examinationmentioning
confidence: 99%
“…Therefore, a threshold of 3/4 was used in the present study. However, the mean GHQ‐12 score in the present study (5.5) was higher than in other studies performed in Japan . The higher cut‐off point of 7/8 was also explored in the present study for increased specificity.…”
Section: Discussioncontrasting
confidence: 55%